The birth of sense : generative passivity in Merleau-Ponty's philosophy - Beith, Don (Series in Continental thought ;, 2018)
In The Birth of Sense, Don Beith proposes a new concept of generative passivity, the idea that our organic, psychological, and social activities take time to develop into sense. More than being a limit, passivity marks out the way in which organisms, persons, and interbodily systems take time in order to manifest a coherent sense.